Elevated symmetric supercapacitor performance and simulated solar light-functioning H2O2 production using single-step fabricated 2D/2D NiAl-based LDH/CoNi-based MOF nanohybrid - Husain A.; Lee D.-E.; Danish M.; Ansari M.N.M.; Shin S.-H.; Lee J.-Y.; Lee J.-W.; Jo W.-K. (Elsevier B.V., 2025)
Combining photocatalytic hydrogen peroxide (H2O2) production with supercapacitors offers a synergistic solution to address both solar-driven catalysis and energy storage challenges. In this connection, this study explored a novel, one-step thermal impregnation method for synthesizing a high-performance nanohybrid material. The unique combination of nickel-aluminum layered double hydroxides (NiAl-L) and Co/Ni-based metal-organic framework (CoNi-M) synergistically enhances electrochemical performance, leading to improved energy storage capacity. Interestingly, the NiAl-L/CoNi-M nanohybrid heterojunction exhibits remarkable characteristics in a three-electrode system, achieving an impressive specific capacitance of 2672.3 Fg?1 at 1 A g?1. It also demonstrates outstanding cyclic stability, retaining 93.6 % of its capacity even after 5000 galvanostatic charge-discharge (GCD) cycles. Moreover, the symmetrical supercapacitor device made of NiAl-L/CoNi-M demonstrates outstanding performance, sustaining 90.9 % capacity after 5000 GCD cycles, with a specific capacitance of 309.7 Fg?1 at 1 Ag?1 and a high energy density of 43 WhKg?1. Additionally, the synergistic combination of NiAl-L and CoNi-M enhances the photocatalytic performance, achieving an H2O2 evolution rate of 334.86 ?mol L?1 h?1 under simulated solar light irradiation. This rate is 2.61, 3.81, and 5.81 times greater than that of pure CoNi-M, Co-M, and NiAl-L, respectively, highlighting the potential of NiAl-L/CoNi-M nanohybrid for sustainable energy application. ? 2024